Synthesis and pharmacological evaluation of N-benzyl substituted 4-bromo-2, 5-dimethoxyphenethylamines as 5-HT2A/2C partial agonists. Issue 14 (15th July 2015) - Hansen, Martin; Jacobsen, Stine Engesgaard; Plunkett, Shane; Liebscher, Gudrun Eckhard; McCorvy, John D.; Bräuner-Osborne, Hans; Kristensen, Jesper Langgaard
Graphical abstract: Abstract: N -Benzyl substitution of phenethylamine 5-HT2A receptor agonists has dramatic effects on binding affinity, receptor selectivity and agonist activity. In this paper we examine how affinity for the 5-HT2A/2C receptors are influenced by N -benzyl substitution of 4-bromo-2, 5-dimethoxyphenethylamine derivatives. Special attention is given to the 2′ and 3′-position of the N -benzyl as such compounds are known to be very potent. We found that substitutions in these positions are generally well tolerated. The 2′-position was further examined using a range of substituents to probe the hydrogen bonding requirements for optimal affinity and selectivity, and it was found that small changes in the ligands in this area had a profound effect on their affinities. Furthermore, two ligands that lack a 2′-benzyl substituent were also found to have high affinity contradicting previous held notions. Several high-affinity ligands were identified and assayed for functional activity at the 5-HT2A and 5-HT2C receptor, and they were generally found to be less efficacious agonists than previously reported N -benzyl phenethylamines.